2022
DOI: 10.3389/fmolb.2022.942402
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a redox-related gene signature for overall survival prediction and immune infiltration in non-small-cell lung cancer

Abstract: Background: An imbalance in the redox homeostasis has been reported in multiple cancers and is associated with a poor prognosis of disease. However, the prognostic value of redox-related genes in non-small-cell lung cancer (NSCLC) remains unclear.Methods: RNA sequencing data, DNA methylation data, mutation, and clinical data of NSCLC patients were downloaded from The Cancer Genome Atlas and Gene Expression Omnibus databases. Redox-related differentially expressed genes (DEGs) were used to construct the prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Clarifying the interplay between genetic alterations and metabolic changes, and their collective role in immune evasion, is pivotal for the development of effective therapies to bypass immunotherapy resistance. Previous studies has found a link between high redox signatures, 24–27 mutations in genes associated with redox homeostasis (such as STK11 or KEAP1), 28–30 and adverse outcomes in lung cancer. However, the dynamic between metabolic states, specific genetic alterations, and TME composition in LUAD has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…Clarifying the interplay between genetic alterations and metabolic changes, and their collective role in immune evasion, is pivotal for the development of effective therapies to bypass immunotherapy resistance. Previous studies has found a link between high redox signatures, 24–27 mutations in genes associated with redox homeostasis (such as STK11 or KEAP1), 28–30 and adverse outcomes in lung cancer. However, the dynamic between metabolic states, specific genetic alterations, and TME composition in LUAD has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, an increasing number of molecular biomarkers have been integrated into models for the prognostic assessment of cancer patients. [4–8] However, the prognostic features and nomographs of multiple mRNA in TSCC patients have not been sufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of molecular biomarkers have been integrated into models for the prognostic assessment of cancer patients. [4][5][6][7][8] However, the prognostic features and nomographs With the development of second-generation sequencing technology, attention has gradually turned to the analysis and alignment of high-throughput sequencing data, leading to the establishment of The Cancer Genome Atlas (TCGA) database, which provides an avenue for tumor-related research through the mining and analysis of genomic data on cancer genes. Initiated and completed by the National Cancer Institute and the National Human Genome Research Institute in the United States, TCGA is a genomic variation map of human tumors obtained through large-scale sequencing of the human tumor genome, containing information on genomics, transcriptomics, epigenetics, proteomics, as well as clinical information.…”
Section: Introductionmentioning
confidence: 99%